2010
DOI: 10.1108/13552541011065704
|View full text |Cite
|
Sign up to set email alerts
|

Redesign and cost estimation of rapid manufactured plastic parts

Abstract: Purpose -The purpose of this paper is to highlight how rapid manufacturing (RM) of plastic parts combined with part redesign could have positive repercussion on cost saving. Design/methodology/approach -Comparison between two different technologies for plastic part production, the traditional injection molding (IM) and the emergent RM, is done with consideration of both the geometric possibilities of RM and the economic aspect. From an extended literature review, the redesign guidelines and the cost model are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 16 publications
3
148
0
1
Order By: Relevance
“…It should be interesting to hypothesize a hybrid production model that includes the post-processing cost of AM, not only in terms of quality controls and support removal but in terms of material removal (Campbell et al, 2012;Manogharan et al, 2015). Existing cost models consider the activities directly connected to building process of AM; however, due to the fact that AM allows the production of end use product, it is important to include in the cost model all the activities involved to the calculation of the full cost of a finish part like, for example, redesign costs (Eleonora Atzeni et al, 2010;Hague et al, 2003) and material removal cost (Manogharan et al, 2016). For this reason, the definition of a new cost model appears necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It should be interesting to hypothesize a hybrid production model that includes the post-processing cost of AM, not only in terms of quality controls and support removal but in terms of material removal (Campbell et al, 2012;Manogharan et al, 2015). Existing cost models consider the activities directly connected to building process of AM; however, due to the fact that AM allows the production of end use product, it is important to include in the cost model all the activities involved to the calculation of the full cost of a finish part like, for example, redesign costs (Eleonora Atzeni et al, 2010;Hague et al, 2003) and material removal cost (Manogharan et al, 2016). For this reason, the definition of a new cost model appears necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Atzeni et al 2010;Hopkinson and Dickens 2003) have concluded that AM processes are more suitable to series production of small parts and found an indirect strong correlation between size and production volume. Surprisingly however, our survey did not reveal any significant statistical correlation between these two variables.…”
Section: Experience In Designing End Use Component In Ammentioning
confidence: 99%
“…There have been some suggestions that AM for plastics can be suitable for production volumes up to tens of thousands (Atzeni et al 2010;Hopkinson and Dickens 2003;Stucker 2011). However, in our survey, the production volumes indicated were typically between 11 and 1000, which is in agreement with the results reported by Karania and Kazmer (2007).…”
Section: Experience In Designing End Use Component In Ammentioning
confidence: 99%
See 1 more Smart Citation
“…When applied in experimental studies, the discussed methods may reduce costs of model fabrication [28]. Models built with the use of the proposed approaches featured a reliable reconstruction of both internal and external anatomical structures.…”
Section: Discussionmentioning
confidence: 99%